Phosphorotioated Oligonucleotides Trigger Synthesis of Human Coagulation Serine Proteases - Bokarewa, Maria I.; Hellstrand, Kristoffer; Tarkowski, Andrej (Thrombosis and Haemostasis, 2002)
CpG containing phosphorotioated oligonucleotides (ODN) are efficient adjuvants able to enhance macrophage and B cell activities. Their impact in the generation of coagulation and fibrinolytic factors has not been analysed.Production of coagulation and fibrinolytic proteins by human peripheral blood mononuclear cells (PBMC) treated with ODN was assessed.ODN induced in vitro generation of tissue factor (TF), thrombin and plasminogen, by PBMC. Synthesis of TF and thrombin occurred mostly in monocytes, while plasminogen was produced by both monocytic and lymphocytic cell populations. Generation of these proteins stimulated by CpG was totally blocked by cycloheximide, indicating the requirement of ongoing protein synthesis. Protein synthesis was equally pronounced at stimulation with cytosine-phosphate-guanosine (CpG)- and GpC- containing ODN, and dependend on the presence of the phosphorotioate moiety backbone in the ODN. Plasminogen, synthesized by monocytes and lymphocytes, was shown to be the primary product of ODN activation, leading subsequently to the expression of TF and thrombin generation.Our findings should be taken into consideration when assessing advantages and drawbacks of immunotherapy and gene therapy.
Keywords: Tissue factor; plasminogen; oligonucleotides